Degradation of Arable Soils in Central Yakutia: Negative Consequences of Global Warming for Yedoma Landscapes - Desyatkin, Roman; Filippov, Nikolai; Desyatkin, Alexey; Konyushkov, Dmitry; Goryachkin, Sergey (Frontiers in Earth Science, 2021)
Global warming, which is especially intensive (up to 0.08°C yr−1) in permafrost area of Central Yakutia, has dramatic consequences for scarce arable land resources in this region. In Yedoma landscapes, intense permafrost thawing on arable fields unprotected by forest vegetation transforms the surface microtopography with the formation of residual thermokarst mounds (byllars) of 6–10 m in diameter surrounded by a polygonal network of hollows of 0.3–1.5 m in depth above melting ice wedges. This process also takes place on former croplands abandoned in the recent decades because of socioeconomic reasons. It is accompanied by a significant transformation of the previously highly likely homogeneous soil cover composed of Cambic Turbic Cryosols (Sodic) into differentiated complexes of permafrost-affected Stagnic Cambisols or Calcic Solonetzes (Turbic) on the mounds and Calcic Stagnic Solonetzes (Turbic) in the microlows. Surface soil horizons on the mounds have a strongly to very strongly alkaline reaction (pH 8.5–9.5) and low (<2%) organic carbon content; a wavy line of effervescence is found at a depth of 15–30 cm. Soils in the microlows have a close to neutral reaction in the upper horizons (pH 6.2–7.5); higher organic carbon content (2–3%); more pronounced textural differentiation of the profile with the formation of typical natric Btn and, in some cases, overlying eluvial E horizons; deeper (50–60 cm) line of effervescence; and clear stagnic features in the lower part of the profile. In the case of shallow embedding by ice wedge, the lowermost part of the soil in the microlow is characterized by the low bulk density (1.04 g cm−3) because of the appearance of hollows after thawing of the ice-rich transient layer and melting of the top of ice wedges. This may be indicative of the further soil subsidence in the future and the appearance of initial thermokarst lakes (dyuedya) within the Yedoma terrain with its transformation into the alas type of landscape. Rapid thermokarst-driven development of microtopography followed by differentiation of the soil cover with increasing soil alkalinity on the microhighs and soil textural differentiation and overmoistening of deep layers in the microlows prevents the return of abandoned arable land to agriculture in Yedoma landscapes.